Benefits of coastal managed realignment for society: Evidence from ecosystem service assessments in two UK regions. (5th October 2020) - MacDonald, Michael A.; de Ruyck, Chris; Field, Rob H.; Bedford, Alan; Bradbury, Richard B.
Abstract: Coastal managed realignment has the potential to deliver both nature conservation and other benefits to people, but these are rarely quantified. We used an ecosystem services assessment toolkit, TESSA, at two locations in the UK; Hesketh Outmarsh West (northwest England), where realignment has already been carried out, and the Inner Firth of Forth (central Scotland), where realignment is proposed for multiple sites. At the Inner Forth we focus on one site, Inch of Ferryton, in Clackmannanshire but also assess ecosystem services across several sites. Using dedicated data collection where possible, and site-appropriate existing data, we estimate the value of these sites to people in the realigned state compared with the most realistic alternative: continued agricultural production behind hard flood defences (agricultural state). Services assessed were climate change mitigation, agricultural production, nature-based recreation, and flood risk protection. At both sites agricultural production was estimated to be greater in the agricultural state, while other services were estimated to be greater in the realigned state. We are cautious about assigning overall monetary values based on biophysical attributes, particularly considering that climate change mitigation is highly sensitive to carbon prices, and that by necessity we were unable to quantify all services. Nevertheless, using a price for carbon that incorporates the societal cost of emissions, we estimate that the net annual provision of services is £262, 935 (£1460.75/ha) at Hesketh Outmarsh West and £93, 216 (£574.70/ha) at Inch of Ferryton. At both sites, sequestered carbon in accreting sediments outweighs greenhouse gas emissions from intertidal habitats, and the net value of this in turn outweighs the income foregone from crops and grazing. At Hesketh Outmarsh West the value of ecosystem services is increased by the reduction to flood risk arising from the coastal managed realignment action. Nature-based recreation is estimated to increase at both sites under realignment, with the visitor profile expected to be strongly local. Decisions about coastal management, including realignment, should incorporate information about the ecosystem services provided under different scenarios. This applies beyond coastal ecosystems, and the site-scale is often the most appropriate scale to carry out such assessments, as this is the scale at which decisions are often taken.